2019
DOI: 10.3389/fimmu.2019.00165
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Is Required for Efficient Control of Coxiella burnetii Infection and Dissemination

Abstract: The intracellular pathogen Coxiella (C.) burnetii causes Q fever, a usually self-limiting respiratory infection that becomes chronic and severe in some patients. Innate immune recognition of C. burnetii and its role in the decision between resolution and chronicity is not understood well. However, TLR2 is important for the response to C. burnetii in mice, and genetic polymorphisms in Myd88 have been associated with chronic Q fever in humans. Here, we have employed MyD88-deficient mice in infection models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…A separate study has revealed similar findings, showing that MyD88 −/− MΦs bear significantly higher bacterial loads at 72 hpi than WT controls, as well as diminished production of IL-6 and IL-10. Together, these results indicate a role of MyD88 in producing both a cytokine response and regulating the bacterial load in MΦs [136]. In that study, after intratracheal infection, the bacterial load of C. burnetii NMII was consistently higher in the lung, spleen, heart, and liver tissues from 7 to 120 dpi; in contrast, MyD88 +/− mice showed complete clearance at 27 dpi [136].…”
Section: Tlr/myd88-mediated Recognitionmentioning
confidence: 71%
See 2 more Smart Citations
“…A separate study has revealed similar findings, showing that MyD88 −/− MΦs bear significantly higher bacterial loads at 72 hpi than WT controls, as well as diminished production of IL-6 and IL-10. Together, these results indicate a role of MyD88 in producing both a cytokine response and regulating the bacterial load in MΦs [136]. In that study, after intratracheal infection, the bacterial load of C. burnetii NMII was consistently higher in the lung, spleen, heart, and liver tissues from 7 to 120 dpi; in contrast, MyD88 +/− mice showed complete clearance at 27 dpi [136].…”
Section: Tlr/myd88-mediated Recognitionmentioning
confidence: 71%
“…Vacuole TLR2 [111,113] Myd88 [112] TLR7 [111] TLR9 [114] NOD2 [113] Coxiella burnetii MyD88 [135][136][137] TLR1 [135] TRIF [137] TLR2 [137,138] Myd88, TRIF [137] TLR4 [137] *Denotes primary mode of transmission.…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, IL-1B, IL-2 and IL-6 are all common interleukins, they play an important role in lymphocytes activation, production of cytokines, antibodies and complement [40][41][42]. And MYD88, IRF1 and TLR4, play key roles in pathogen recognition, activation and conduction of immune signals [43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…This latter program is characterized by the low production of inflammatory cytokines and the overproduction of immunoregulatory cytokines, such as interleukin (IL)-10, which is associated with persistent infection in tissues from mice overexpressing IL-10 ( Meghari et al, 2008 ) and persistent Q fever in humans ( Honstettre et al, 2003 ). More recently, in intraperitoneal or intratracheal infection of Myd88 –/– mice, persistence of C. burnetii has been observed in organs with less granulomatous inflammation and decreased expression of several genes involved in the intracellular control of bacteria ( Kohl et al, 2019 ). C. burnetii also affects the functions of the dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%